Flukicidal effects of abietane diterpenoid derived analogues against the food borne pathogen Fasciola hepatica. - Gilda Padalino (Veterinary Parasitology, 2022)
Control of liver fluke infections remains a significant challenge in the livestock sector due to widespread distribution of drug resistant parasite populations. In particular, increasing prevalence and economic losses due to infection with Fasciola hepatica is a direct result of drug resistance to the gold standard flukicide, triclabendazole. Sustainable control of this significant zoonotic pathogen, therefore, urgently requires the identification of new anthelmintics. Plants represent a source of molecules with potential flukicidal effects and, amongst their secondary metabolites, the diterpenoid abietic acids can be isolated in large quantities. In this study, nineteen (19) chemically modified abietic acid analogues (MC_X) were first evaluated for their anthelmintic activities against F. hepatica newly excysted juveniles (NEJs, from the laboratory-derived Italian strain); from this, 6 analogues were secondly evaluated for their anthelmintic activities against adult wild strain flukes. One analogue, MC010, was progressed further against 8-week immature- and 12-week mature Italian strain flukes. Here, MC010 demonstrated moderate activity against both of these intra-mammalian fluke stages (with an adult fluke EC50 = 12.97 µM at 72 h post culture). Overt mammalian cell toxicity of MC010 was inferred from the Madin-Darby bovine kidney (MDBK) cell line (CC50 = 17.52 µM at 24 h post culture) and demonstrated that medicinal chemistry improvements are necessary before abietic acid analogues could be considered as potential anthelmintics against liver fluke pathogens